2021
DOI: 10.3389/fonc.2021.740661
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Impact of Inter-Fraction Anatomical Changes in Carbon Ion Boost Treatment for High-Risk Prostate Cancer (AIRC IG 14300)

Abstract: Rectum and bladder volumes play an important role in the dose distribution reproducibility in prostate cancer adenocarcinoma (PCa) radiotherapy, especially for particle therapy, where density variation can strongly affect the dose distribution. We investigated the reliability and reproducibility of our image-guided radiotherapy (IGRT) and treatment planning protocol for carbon ion radiotherapy (CIRT) within the phase II mixed beam study (AIRC IG 14300) for the treatment of high-risk PCa. In order to calculate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Other studies use PTV for interfractional dose assessment 23 , 25 , 35 ; however, we evaluated target coverage using CTV. The International Commission on Radiation Units & Measurements (ICRU) Report 78 defines internal margins to compensate for internal uncertainties such as physiologic movement and variations in size, shape, and position of the CTV and uncertainties in factors external to the patient such as setup error 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies use PTV for interfractional dose assessment 23 , 25 , 35 ; however, we evaluated target coverage using CTV. The International Commission on Radiation Units & Measurements (ICRU) Report 78 defines internal margins to compensate for internal uncertainties such as physiologic movement and variations in size, shape, and position of the CTV and uncertainties in factors external to the patient such as setup error 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Russo et al . evaluated interfractional dose distribution using serial cone-beam CT with bony structure registration, and concluded that dose variations due to rectal and bladder volume variations could be improved by image guidance 35 . However, interfractional change resulted in degraded target coverage for some fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scans were acquired using a Philips Brilliance Big Bore CT scanner according to our clinical protocol and registered with multiparametric magnetic resonance imaging (mpMRI). Prior to treatment simulation and delivery, patients were asked to follow a preparation protocol similarly to Russo et al [17] to limit prostate mobility and achieve anatomical reproducibility (full bladder, empty rectum). The clinical target volume (CTV) was defined as the whole prostate and the proximal 5–10 mm of seminal vesicles.…”
Section: Methodsmentioning
confidence: 99%
“…At CNAO, patients with high-risk prostate cancer are currently treated with 66.4 GyRBE for CIRT delivered in 16 sessions, as derived from the NIRS schedule. We participated in a phase II feasibility study (NCT02672449) of a mixed-beam approach including an anticipated CIRT boost (16.6 GyRBE in 4 fractions), followed by pelvic photon IMRT (up to 50 Gy) for high-risk prostate cancer [53,54], thereby showing promising preliminary feasibility and safety findings. Indeed, no gastrointestinal or genitourinary toxicities were recorded after 1 and 3 months from the whole course of RT.…”
Section: Prostate Cancermentioning
confidence: 99%